Information System Self Acces Center (SAC) Language Center Muhammadiyah University Bengkulu - Rio Eko Prayuda; Surya Ade Saputera (Jurnal Komputer, Informasi dan Teknologi, 2022)
Self Access Center (SAC) is an independent learning tool to access various knowledge outside the acquisition of material in the central classroom to access various knowledge independently without teacher guidance. Self Access Center Language Center University of Muhammadiyah Bengkulu (UMB) is one of the training and test institutions in Bengkulu, Self Access Center data processing requires a lot of accuracy so that there are no errors in data processing. The Self Access Center (SAC) of the University of Muhammadiyah Bengkulu said that there was no information system for processing the Self Access Center (SAC) data, all the TOEFL Self Access Center (SAC) test registration processes were still carried out manually. This study examines how to design a Self Access Center Information system for the Language Center of the University of Muhammadiyah Bengkulu. The purpose of this study was to design a Self Access Center Information system for the Language Center of the University of Muhammadiyah Bengkulu. The development model used is the Rapid Application Development (RAD) method. PHP programming language and MySQL database have been well designed so that they can be implemented. The results of this study are the new system replaces the old system by overcoming the weaknesses in the manual system (the old one), then the system provides convenience for UMB Self access center administrative officers in accessing stock and making reports, thus making the work of UMB Self access center administrative officers be effective and efficient.